Investigation of Star Gooseberry (Phyllanthus Acidus) Wine Production - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
The star gooseberry fruit is pendulous, bear in small clusters from the branches, round or slightly flattened at the poles. Gooseberry fruit is rich in antioxidants including ascorbic acid and phenolic compounds. It is an important herbal medicine due to its effective antiviral activities. Effect of primary fermentation temperature (26oC, 28oC, 30oC, 32oC), sugar to pulp ratio (4, 8, 12, 16% w/w), Saccharomyces cerevisiae inoculation (1.0 x 108,1.5 x 108, 2.0 x 108, 2.5 x 108 cfu/g) on ascorbic acid (mg/ 100 mL), total phenolic content (mg GAE/ 100 mL) and total ﬂavonoid (mg CE/ 100 mL) content of Phyllanthus acidus wine were thoroughly investigated. The aging (1, 2, 3, 4 weeks) was also examined to improve the turbidity (mJ/cm2) and sensory score of wine. The optimal conditions for fermentation of Phyllanthus acidus juice should be conducted at 12 days of primary fermentation with 12% of sugar supplementation inoculated with 2.0 x 108 cfu/ml of Saccharomyces cerevisiae and 4 weeks of aging to get pleasant physico-chemical characteristics of Phyllanthus acidus wine. Phyllanthus acidus wine was red-pink, clear and transparent. This present study revealed that horticulture farmers would get more added values from Phyllanthus acidus fruits not only by local commerce but also processing. It could be processed by fermentation and conversion into high valued wine.Keywords: Phyllanthus acidus, Wine, Fermentation, Sacchromyces cerevisiae, Ascorbic acid, Phenolic, flavonoid.